2008
DOI: 10.1063/1.2884529
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic, and electronic properties of Fe3C from first principles

Abstract: Using first-principles calculations within the generalized gradient approximation, we predicted the lattice parameters, elastic constants, vibrational properties, and electronic structure of cementite (Fe 3 C). Its nine single-crystal elastic constants were obtained by computing total energies or stresses as a function of applied strain. Furthermore, six of them were determined from the initial slopes of the calculated longitudinal and transverse acoustic phonon branches along the [100], [010] and [001] direct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 48 publications
5
91
3
Order By: Relevance
“…Our calculated values are in good agreement with previously calculated C ij s of Fe 3 C. 37,38 However, Lv et al 39 reported that C 44 is negative. Barring any typographical error, their C ij values of predict that Fe 3 C is elastically unstable, which is inconsistent with both present and previous calculations.…”
Section: B Single-crystal Elastic Constants and Isotropic (Polycrystsupporting
confidence: 82%
See 2 more Smart Citations
“…Our calculated values are in good agreement with previously calculated C ij s of Fe 3 C. 37,38 However, Lv et al 39 reported that C 44 is negative. Barring any typographical error, their C ij values of predict that Fe 3 C is elastically unstable, which is inconsistent with both present and previous calculations.…”
Section: B Single-crystal Elastic Constants and Isotropic (Polycrystsupporting
confidence: 82%
“…Barring any typographical error, their C ij values of predict that Fe 3 C is elastically unstable, which is inconsistent with both present and previous calculations. 37,38 Recently, Grimvall et al 68 have discussed the issue of elastic instability and its relation to phonon instability in a number of materials. Besides classic cases of bcc-Ti, Hf and Zr, authors have discussed other cases as well.…”
Section: B Single-crystal Elastic Constants and Isotropic (Polycrystmentioning
confidence: 99%
See 1 more Smart Citation
“…Random orientations distribution of lattice in ferritic grains was assumed. In the case of cementite only theoretical (ab initio calculation) tensor of single crystal elastic constants (C ij ) is available [31]. However, the theoretical data (averaged for polycrystalline aggregate) does not agree with experimentally determined Young's modulus (E) and Poison's ratio (m) [32,33].…”
Section: Model Parametersmentioning
confidence: 97%
“…Electronic, structural, and magnetic properties of pure cementite were described in many previous communications. [7,[10][11][12] Furthermore, there are detailed studies of thermodynamic properties of pure cementite, [9,13] elastic properties, [14][15][16][17] point defects, and possible C diffusion paths. [12] The energetics and electronic structure of impurity substituted cementite have also been the focus of a considerable number of previous studies.…”
Section: Introductionmentioning
confidence: 99%